Sub-3 nm particle size and composition dependent response of a nano-CPC battery - J. Kangasluoma; C. Kuang; D. Wimmer; M. P. Rissanen; K. Lehtipalo; M. Ehn; D. R. Worsnop; J. Wang; M. Kulmala; T. Petäjä (Atmospheric Measurement Techniques, 2014)
In this study we built a nano-CPC (condensation particle counter) battery, consisting of four ultrafine CPCs optimized for the detection of sub-3 nm particles. Two of the CPCs use diethylene glycol as a working fluid: a laminar type diethlylene glycol CPC and a mixing type Airmodus A09 particle size magnifier. The other two CPCs are a laminar type TSI 3025A and a TSI 3786 with butanol and water as the working fluids, respectively. The nano-CPC battery was calibrated with seven different test aerosols: tetraheptyl ammonium bromide, ammonium sulfate, sodium chloride, tungsten oxide, sucrose, candle flame products and limonene ozonolysis products. The results show that ammonium sulfate and sodium chloride have a higher activation efficiency with the water-based 3786 than with the butanol-based 3025A, whereas the other aerosols were activated better with butanol than with water as the working fluid. It is worthwhile to mention that sub-2 nm limonene ozonolysis products were detected very poorly with all of the CPCs, butanol being the best fluid to activate the oxidation products. To explore how the detection efficiency is affected if the aerosol is an internal mixture of two different chemical substances, we made the first attempt to control the mixing state of sub-3 nm laboratory generated aerosol. We show that we generated an internally mixed aerosol of ammonium sulfate nucleated onto tungsten oxide seed particles, and observed that the activation efficiency of the internally mixed clusters was a function of the internal mixture composition.